Evaluating the quality of multiple‐choice question pilot database: A global educator‐created tool for concept‐based pharmacology learning - Adeladlew Kassie Netere; Tony Hughes; Anna‐Marie Babey; Martin Hawes; Janet Mifsud; John P. Kelly; Willmann Liang; Mark Hernandez; Kelly Karpa; Hesham Al‐Sallami; Lynette B. Fernandes; Patrik Aronsson; et al. (Wiley, 2024)
Abstract The Core Concepts of Pharmacology (CCP) initiative is developing educational resources to transform pharmacology education into a concept‐based approach. This study evaluated the quality of global educator‐created MCQs in generating items for the pharmacology concept inventory (PCI) instrument and developed as a resource for learning pharmacology fundamental concepts. A panel of 22 global pharmacology experts recruited from the CCP initiative research team participated in the MCQ pilot database design and evaluation. The quality analysis framework of the MCQs in the pilot database included four assessment tools: item writing guidelines (IWGs), Bloom's taxonomy, the CCP, and the MCQ design format. A two‐phase evaluation process was involved, including inter‐rater agreement on item quality, followed by resolving conflicts that occurred in quality assessment. The chi‐square (χ2) test of independence and Cramer's V correlation tests were utilized to measure the relationship among quality assessment attributes. About 200 MCQs were gathered and 98% underwent expert evaluation. Nearly 80% addressed one or more CCP, with 52% designed using a context‐dependent format. However, only 40% addressed higher levels of Bloom's cognitive domain and 10% adhered to all IWGs. A strong positive correlation was observed between the context‐based item format and its effectiveness in assessing the higher cognitive domain, the main CCP and improved IWGs adherence. Context‐based item construction can assess the higher cognitive skills and fundamental pharmacology concepts, showing potential for rigorous PCI development. The pilot database will store items to create the PCI, aiding the development of a concept‐based pharmacology curriculum.